Housekeeper’s Work Migration in Southeast Asia - the Philippines Case (Global Journal of Human-Social Science, 2022)
This paper focuses on understanding the economic migration of Philippino women to the transnational market of household work We base our research on the feminist literature on reproductive labor using a review of scholarship as a tool to understand the structural and statal elements that help to keep this flux in pace We choose the Philippines from a broader look at southeast Asia both because it is a country considered a regional model in migration governance and because of its sheer number of outflow migrants Our study method consists of a case study through which we focus on news taken from the Philippine Overseas Employment Administration website to reveal the positioning of the State on the governance of Philippino migrant women and its nuances at that
Keywords: economic migration; philippines; reproductive labor; migration governance